Spatial bias in figure placement in representational drawing: Associations with handedness and script directionality. Issue 5 (3rd September 2019) - Faghihi, Nafiseh; Garcia, Omar; Vaid, Jyotsna
ABSTRACT: Spatial biases in graphomotor production tasks such as figure drawing may reflect biological (cerebral lateralization), biomechanical (limb movement), and/or cultural (reading/writing direction) influences. The present study examined sources of bias in the placement in graphic space of a symmetrical drawn figure (a tree). A previous study using a child sample found an overall leftward placement bias, independent of participants' reading/writing direction experience [Picard & Zarhbouch, 2014. Leftward spatial bias in children's drawing placement: Hemispheric activation versus directional hypotheses. Laterality: Asymmetries of Body, Brain and Cognition, 19 (1), 96–112]; moreover, the left-side bias was greater in right handers. Using an adult sample, the present study also found an overall left placement bias. This effect was significantly greater in right-handed than left-handed participants. Importantly, a left placement bias was significantly greater in left-to-right readers (English) than in participants whose first learned language was from right-to-left (Urdu, Arabic or Farsi). The fact that script directionality is associated with figure placement in our study but not in the previous study suggests that a certain threshold of experience in reading/writing in a given direction may be needed for scanning biases to exert a demonstrable effect on representational drawing. These findings suggest that biomechanical and cultural factors offer a more parsimonious account of spatial biases in drawing.